2023
DOI: 10.3390/app13053128
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bayesian Neural Network (BNN) for the Prediction of Blast-Induced Ground Vibration

Abstract: Rock blasting is one of the most common and cost-effective excavation techniques. However, rock blasting has various negative environmental effects, such as air overpressure, fly rock, and ground vibration. Ground vibration is the most hazardous of these inevitable impacts since it has a negative impact not only on the environment of the surrounding area but also on the human population and the rock itself. The PPV is the most critical base parameter practice for understanding, evaluating, and predicting groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The BNN and ANN models show better performance than Xgboost models during the testing phase, and BNN models have higher comprehensive predicting performance than other models in the prediction phase of five key structural and sustainable performance indicators. Similar results are shown in the work by Fissha, et al [59], which showed that the BNN models outperformed traditional neural networks with noisy datasets.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The BNN and ANN models show better performance than Xgboost models during the testing phase, and BNN models have higher comprehensive predicting performance than other models in the prediction phase of five key structural and sustainable performance indicators. Similar results are shown in the work by Fissha, et al [59], which showed that the BNN models outperformed traditional neural networks with noisy datasets.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Finally, the output nodes generate the results. Fissha [ 64 ] elucidated that the training of ANN entails the fine-tuning of weights in accordance with the network's performance in achieving desired outcomes, with the objective of maximizing accuracy. Several authors have embraced this strategy over the years.…”
Section: Model Development Methodologymentioning
confidence: 99%
“…These networks fit nonlinear and perceiving patterns 87 . Fissha et al 88 introduced the application of Bayesian-based ANN to improve the Mikurahana quarry blasting impact, demonstrating a new advantage of neural networks for ground improvement. Bhatawdekar et al 89 developed a soft computing model for estimating fly rock distance using different input variables, such as hole diameter, burden, stemming length, rock density, charge-per-meter, powder factor (PF), blast-ability index (BI), and weathering index datasets using hybrid ANN approaches.…”
Section: Data Analysis and Soft Computing Approachesmentioning
confidence: 99%